Characterization of the genetic environment of blaESBL genes, integrons and toxin-antitoxin systems identified on large transferrable plasmids in multi-drug resistant Escherichia coli - Wang, Juan; Stephan, Roger; Zurfluh, Katrin; Hächler, Herbert; Fanning, Séamus (Frontiers in Microbiology, 2015)
Abstract- Objectives: Previously 14 conjugative plasmids from multi-drug resistant (MDR) Escherichia coli from healthy humans and food-producing animals in Switzerland were sequenced. The aim of this study was to extend the genetic characterization of these plasmids with a focus on blaESBL genes including blaCTX-M-1 and blaTEM, class 1 integrons and toxin-antitoxin (TA) systems contained therein. Methods: The nucleotide sequences and subsequent annotation therein of 14 conjugative plasmids were previously determined from their corresponding transconjugants. The TA loci were confirmed by RASTA-Bacteria. Results: Eight of the conjugative plasmids identified were found to encode genes expressing ESBLs. Structural heterogeneity was noted in the regions flanking both the blaCTX-M-1 and blaTEM genes. The blaCTX-M-1 genes were associated with the common insertion sequences ISEcp1 and IS26, and uniquely with an IS5 element in one case; while blaTEM genes were found to be associated with IS26 and Tn2. A new blaTEM-210 gene was identified. Seven class 1 integrons were also identified and assigned into 3 groups, denoted as In54, In369 and In501. Fourteen TA loci belonging to 4 of the TA gene families (relBE, vapBC, ccd and mazEF) were identified on 10 of these plasmids. Conclusions: Comparative sequence analysis of these plasmids provided data on the structures likely to contribute to sequence diversity associated with these accessory genes, including IS26, ISEcp1 and Tn2. All of them contribute to the dissemination of the corresponding resistance genes located on the different plasmids. There appears to be no association between β-lactam encoding genes and TA systems.